2023
DOI: 10.1021/acs.joc.2c02575
|View full text |Cite
|
Sign up to set email alerts
|

Amide-Ligand-Promoted Silver-Catalyzed C–H Fluorination via Radical/Polar Crossover

Abstract: We describe an efficient method for benzylic C−H fluorination via sequential hydrogen-atom transfer (HAT) and oxidative radical-polar crossover utilizing the Ag(I)/Selectfluor system. Amide ligands, such as benzamide and sulfonamide, substantially facilitate the processes leading to a carbocation intermediate, which subsequently reacts with nucleophilic fluorinating reagent to form a C−F bond. This protocol is applicable to the fluorination of all 1°, 2°, and 3°C−H bonds as well as to late-stage C−H fluorinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 77 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…Recently, the Hamashima group disclosed a strategy for benzylic C—H fluorination using silver‐catalysis with selectfluor as an oxidant and fluoride as fluorine source (Scheme 52). [ 122 ] The authors found that amide ligands, such as benzamide and sulfonamide, significantly improve the reaction efficiency and selectivity by facilitating the formation of carbocation intermediate. The reaction also occurs via a radical‐polar crossover process, and can be used for late‐stage fluorination of bioactive molecules.…”
Section: Nucleophilic Fluorination Reagentsmentioning
confidence: 99%
“…Recently, the Hamashima group disclosed a strategy for benzylic C—H fluorination using silver‐catalysis with selectfluor as an oxidant and fluoride as fluorine source (Scheme 52). [ 122 ] The authors found that amide ligands, such as benzamide and sulfonamide, significantly improve the reaction efficiency and selectivity by facilitating the formation of carbocation intermediate. The reaction also occurs via a radical‐polar crossover process, and can be used for late‐stage fluorination of bioactive molecules.…”
Section: Nucleophilic Fluorination Reagentsmentioning
confidence: 99%
“…In 2023, Hamashima and co-workers disclosed an analogous, non-photochemical, silver-catalysed HAT radical-polar crossover mechanism for nucleophilic benzylic fluorination ( Figure 34 ) [ 85 ]. The authors proposed a similar mechanistic pathway to the photochemical methods, citing the use of amide ligands as important for modulating the silver catalyst stability and oxidation potentials.…”
Section: Reviewmentioning
confidence: 99%
“…Inspired by their work, we envisioned that the corresponding alkoxylation would also be possible, if a silyl ether could scavenge the fluoride ion and instead liberate an alkoxide nucleophile (Scheme 1). In conjunction with our recent silver‐catalyzed benzylic C−F bond‐forming reaction via radical‐polar crossover, [2x] we herein present an efficient and metal‐free approach for benzylic C(sp 3 )−H alkoxylation. This method enables the incorporation of ether functional groups at primary, secondary, and tertiary benzylic positions, and is suitable for late‐stage C(sp 3 )−H alkoxylation of bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%